Preparation technology and properties of microtexture diamond-coated tools. (November 2018) - Xiang, Daohui; Feng, Haoren; Guo, Zhenhai; Zhang, Lei; Wu, Bangfu
Abstract: Diamond-coated tools are quite lucrative for machining of non-ferrous alloys and advanced composite materials. This paper is focused on the preparation technology and characterization of microtexture diamond-coated tools with advanced cohesive and wear-resistance parameters. Microtextures were processed on the rake face of carbide milling inserts (YG6, WC-6%Co) by laser marking machine. Tools with and without microtexture were considered as two different kinds of substrates. Diamond films were deposited on the substrates by the hot filament chemical vapor deposition (HFCVD). Before deposition, the substrates were pretreated by a two-step ultrasonic assisted acid-alkali etching. The microtexture diamond-coated, conventionally coated, and uncoated carbide tools were used to carry out milling tests on carbon fiber reinforced plastics (CFRP). Experimental results show that the microtextures can enhance the adhesion between the diamond films and the tool surfaces. The microtexture diamond-coated tools have a longer tool life and a better cutting performance than uncoated tools and conventionally coated tools, the surface of CFRP after machined has high quality. What's more, the more complex shape and higher occupied area ratio of the texture are, the longer service life of microtexture diamond-coated tools would be. Graphical abstract: Unlabelled Image Highlights: A novel preparation technology of microtexture diamond-coated tools (MDCT) is proposed. Microtextures improve the adhesion between diamond film and substrate. MDCT have higher wear resistance than conventionally coated tools. MDCT with elliptical-ring shaped grooves have higher wear resistance and service life than those with rectilinear grooves.